Re-imagining the future of transformative learning theory for underrepresented communities - Khupe, Constance; Nyamupangedengu, Eunice (Adult Education Critical Issues, 2024)
This paper is a reflection of our understanding of Jack Mezirow’s theory of transformative learning. Both our present understanding (and interpretation) of, and our re-imagining of the potential that the theory holds, are informed by our identity as African women. Although, that identity suggests underrepresentation, we also see in it agency and potential to bring in additional analytic tools that stem from our way of knowing, living and being.